AI ethics in the law: towards a legal framework for sexual autonomous robots - Rivers, ILG (2023)
The academic and public debate surrounding the ascription of legal personhood—viz., the capacity to hold legal rights and/or to bear legal responsibilities—to autonomous robots has so far focused on developing an appropriate legal framework to regulate wrongs caused by those robots. In this thesis, I shift the focus: I argue that we need to develop an appropriate legal framework to regulate wrongs inflicted on those robots.